Transformative Learning Intervention: Effect on Functional Health Literacy and Diabetes Knowledge in Older African Americans - Daphne W. Ntiri; Merry Stewart (Adult Education Research Conference, 2010)
This study evaluated the effect of a transformative learning intervention on functional health literacy and diabetes knowledge in older African Americans. Twenty participants from senior community centers completed a six session intervention and three health literacy tests. Participants’ verbal responses affirmed the positive influence of the TL principles.